The Effectiveness Of Drawing Chart And Ava As A Health Promotion Media For Increasing Hiv/Aids Knowledge Of Smp N 9 Purwokerto Students At Banyumas Regency - Siti Mulidah; Asrin Asrin; Aris Fitriani (Jurnal LINK, 2013)
Backgraund: HIV/AIDS cases suffer from early younger. AIDS comision (2011) noted that the total HIV/AIDS in Banyumas were 471 patients, which were 264 men and 207 women. This study aim to know the effectiveness of drowing chart and AVA as health promotion media for increasing HIV/AIDS knowledge of SMP N 9 Purwokerto students at Banyumas Regency. Methode: This study is a quasi experimental study with two groups pre and post test static design. Population of this study were all SMP N 9 Purwokerto students of 2012 year, which is 720 students. Sampling methode by rondom sampling tecniq , which was 60 respondents, consist of 30 intervention group drowing chart and 30 intervention group AVA media. The data was analised by univariable (prosentage) and bivariable (pair t test). Result: The knowledge of respondents before and after intervention by using AVA media was increase for 22,83, and by using drowing chart was 27,00. There was not differences of knowledge of men and women befor after intervensi by using drowing chart and AVA media (p=0,062). The effectiveness of drowing chart and AVA as health promotion media for increasing HIV/AIDS knowledge was not differences staticly (p=0,228). Conclution: Staticly, there was not significant result of the effectiveness drowing chart and AVA as health promotion media for increasing HIV/AIDS knowledge of SMP N 9 Purwokerto students. However drowing chart was more better for increasing knowledge and activity of student learn than AVA media.